Hybridité dialogique et métissage culturel dans Mes Règlements de conte (2010) et Le monstre – Le gène d’Adam (2012) de Christopher Di Omen - Sinclair Parfait DASSE BOHO (Revue Hybrides)
This contribution attempts to show that Christopher Di Omen’s writings are cultural objects imbued with hybridity. Indeed, codified by an inter-artistic partnership, Di Omen’s books are often illustrated by the painters Borg and Lapointe. Then, the pictorial rewriting implemented by the pictorial illustration process allows to identify and demarcate the configurations of intermedial dynamics that start from the imbrication of arts towards a dialogue, even a trilogue or a polylogue, between literary genres, spaces-times mobilized and discourse’s categories imbricated within the text. Thus, the literary text, leaning on the text-painting relationship, goes beyond the orthodox scriptural framework to be part and structure of a postmodern avant-garde movement, depending on a generalized dialogism. Through intermedial and dialogical theories, we demonstrate that Di Omen’s books deriving from an aesthetic dynamics heightened supplemented by generic, chronotopic and linguistic crossbreeding possibilities, corollary a plural hybridity.